Incidencia del balance social y ambiental a partir del balance financiero para empresas industriales del departamento de Itapúa (Journal on studies and research of academic knowledge, 2019)
This research was carried out with the purpose of "Analyzing the Incidence of the Social Balance and the Environmental Balance from the Financial Balance for Industrial Companies in the Department of Itapúa", through the application of the descriptive method, selecting the main characteristics of the object of study and each of its parts. The objective was studied from various perspectives: the managers and accounting professionals of industrial companies, professionals who are experts in cooperative entities and in environmental impact, representatives of the Association of Administrators and other accounting professionals, who constituted the population under study. The study was limited to 3 (three) industrial companies in the Department of Itapúa. The Matrix for the Preparation and Evaluation of the Social Balance and the Environmental Balance from the Financial Balance Sheet was implemented and it was concluded about the importance of its preparation and presentation as well as about its effect on several dimensions: for adequate and timely decision making in companies; to know the impact of the business presence in its environment, its social and environmental commitment, nationally and internationally; to generate social and environmental awareness in similar companies, and other impact factors in public and private organizations related to the subject. The need for professional commitment in the dissemination of the proposed tool was also proven.
Keywords: Financial Balance Sheet; Social Balance Sheet; Environmental Balance Sheet; Evaluation Indicator Matrix